2017
DOI: 10.1007/s00167-017-4437-6
|View full text |Cite
|
Sign up to set email alerts
|

Serial clinical and MRI examinations after arthroscopic rotator cuff reconstruction using double-row technique

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…We speculated that a possible explanation might be the effect of decreased inflammation 24 (less water concentration) and tendon loading during the postoperative period after rehabilitation or daily activities. 47 These results are consistent with the findings of Pfalzer et al 37 and Malavolta et al 33 They demonstrated that it took 6 months until the repaired tendon showed normal signals, although their studies did not use quantitative MRI method.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We speculated that a possible explanation might be the effect of decreased inflammation 24 (less water concentration) and tendon loading during the postoperative period after rehabilitation or daily activities. 47 These results are consistent with the findings of Pfalzer et al 37 and Malavolta et al 33 They demonstrated that it took 6 months until the repaired tendon showed normal signals, although their studies did not use quantitative MRI method.…”
Section: Discussionsupporting
confidence: 86%
“…The region of interest was manually drawn according to a method published previously. 37 Specifically, the region of interest was located directly over the medial-row anchor on the coronal-oblique UTE-T2* images (Figure 1). All segmentations on UTE-T2* images were performed by a musculoskeletal radiologist (Y.X.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slice in which the anchor was fully imaged was selected for all measurements. 41 To quantify the normalized SI of the tendon, the SNQ was calculated with the following equation: SNQ = SI of tendon / signal of background. 27 Therefore, the SNQ of the distal supraspinatus tendon (SNQd) and the SNQ of the proximal supraspinatus tendon (SNQp) were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to intramedullary nailing in MIPO, MIPO rarely causes postoperative knee pain and is gradually accepted by more and more orthopaedic surgeons. Therefore, it is believed that the reconstruction of the rotator cuff function by non-absorbable suture technique has certain clinical significance [12][13][14][15] . The purpose of this study was to compare the clinical and radiographic outcomes of auxiliary tension suture fixation to MIPO in PHF.…”
mentioning
confidence: 99%